Faktor yang Memengaruhi Penerapan Electronic Medical Record terhadap Pendaftaran Pasien Rawat Jalan di Rumah Sakit Swasta Jakarta Utara Tahun 2025 - Rhea Renata Anindita; Eka Yoshida; Tinon Ambarini (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Electronic Medical Record (EMR) is an essential component of hospital digital transformation aimed at improving administrative efficiency and service quality. This study aims to analyze the factors influencing the implementation of EMR in outpatient registration at a private hospital in North Jakarta. A mixed-methods design was employed, combining quantitative data collected from questionnaires completed by 30 registration staff with qualitative data obtained through structured interviews and direct observation. The logistic regression analysis revealed that Training and Staff Competence (X2) had a significant positive effect on outpatient registration (OR 30.663; p=0.040), while System Integration and Data Security (X4) also showed a significant effect (OR 15.121; p=0.047). In contrast, Technological Infrastructure Readiness (X1) was positive but not significant (p=0.112), and Organizational Culture and Managerial Support (X3) was negative and not significant (p=0.954). Simultaneously, the model explained 72.1% of the variation in registration effectiveness (Nagelkerke R²=0.721) with a classification accuracy of 93.3%. Qualitative findings supported the quantitative results, highlighting insufficient staff training, persistent technical issues in BPJS system bridging, and difficulties faced by elderly patients in adapting to digital registration. Elderly patients still required staff assistance and simple educational media such as tutorial videos displayed in hospital waiting areas. This study concludes that staff competence and system integration are the key determinants of successful EMR implementation in outpatient registration. It is recommended that hospitals strengthen continuous training programs, improve network and server stability, and expand patient education initiatives to ensure effective, efficient, and patient-friendly digital services.